PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA MATERI RANTAI MAKANAN DAN EKOSISTEM DI SEKOLAH SD 13/1 - Apriliansyah irsan zati; Delan niatra; Airindu zahratul fajriah; Sofinatun hasanah; Khoirunnisa (STKIP Subang, 2026)
This study aims to describe the implementation of the Project Based Learning (PBL) model in science education (IPAS) and its impact on the understanding and learning activities of fifth-grade students at SDN 13/1 Batanghari. The study was conducted over two weeks using observation and semi-structured interviews with 26 students of class V B. The results indicate that the implementation of PBL, combined with video media and collaborative activities, can enhance conceptual understanding, active participation, and students’ teamwork skills. Learning became more engaging, contextual, and fostered scientific attitudes. Therefore, PBL is proven effective in developing students’ independence, responsibility, and critical thinking skills in the topics of food chains and ecosystems.